Nutritional status assessment of elderly residents of Fortaleza,CE, Brazil: the use of different anthropometric indicators - Tarciana Nobre de Menezes; José Maria Pacheco de Souza; Maria de Fátima Nunes Marucci (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p315 The aim of this study was to evaluate the anthropometric variables of elderly people in Fortaleza. This is a populational, cross-sectional household-based study with collection of primary data. The anthropometric variables analyzed were: body mass index (BMI), triceps skinfold thickness (TST) and arm muscle circumference (AMC). Nutritional status was defined from the anthropometrics variables and diagnosed as: eutrophic (elderly whose BMI,TST and AMC simultaneous measures was identified as eutrophic) and non-eutrophic (other elderly people). The sample for the study was composed of 385 selected dwellings, at which 483 elderly people were interviewed (68% of them women). As regards BMI, 47.3% of the elderly concerned were considered eutrophic. A higher proportion of the women had excessive BMI (21.9%) than the men (13.5%). There was a statistically significant association between BMI adequation and sex. The TST measurements indicated that 54.4% of the elderly were eutrophic. No statistically significant association was noted between TST adequation and sex. As for AMC, the men presented a higher prevalence of desnutrition (66.5%) than the women (40.6%). A statistically significant association between AMC adequation and sex was found. With respect to nutritional status, it was observed that 83.9% of the men and 74.2% of the women were classified as non-eutrophic. There was a statistically significant association between nutritional status and sex. The elderly population of Fortaleza exhibit a vulnerable nutritional status in view of the prevalence of non-eutrophic individuals.